UJI EFEKTIVITAS Trichoderma CAIR UNTUK MENGENDALIKAN PENYAKIT Fusarium oxyforum f.sp., cepae DAN PENGARUH TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium cepa L. Aggregatum) - Nahru, Nurfadilah; Rosmini, Rosmini; Lakani, Irwan (Fakultas Pertanian, Universitas Tadulako, 2024)
The objective of this research was to investigate the ability of Trichoderma harzianum to suppress the growth of Fusarium oxysporum f.sp. cepae, which causes damage to red onion crops. The study was conducted in Sidera Village, Sigi Biromaru Subdistrict, Sigi Regency, Central Sulawesi Province, and at the Plant Disease Laboratory, Faculty of Agriculture, Tadulako University, Palu, from August to December 2021. A randomized complete block design (RCBD) was employed, with six treatments: P1 (10-3 dilution, immersion), P2 (10-3 dilution, immersion and one foliar application), P3 (10-3 dilution, immersion and two foliar applications), P4 (10-6 dilution, immersion), P5 (10-6 dilution, immersion and one foliar application), and P6 (10-6 dilution, immersion and two foliar applications). Each treatment was replicated three times, resulting in 18 experimental units. The results indicated that the combination of immersion and foliar application at a 10-3 concentration was effective in suppressing the pathogen's growth and reducing moler disease incidence. Moreover, the 10-3 concentration was more efficient in enhancing onion growth and yield compared to the 10-6 concentration, likely due to its faster or more targeted application.